Fargesia nana (Poaceae, Bambusoideae), a new bamboo species from Yunnan, China - Jian-Wei Li; Juan Wang; Ming Shi; Fan Du (PhytoKeys)
Fargesia nana (Bambusoideae), a new bamboo species is described and illustrated from Wuding County, Yunnan, China. Based on careful comparison of morphological features and molecular phylogeny evidence, we confirmed its identity as a new member of the genus Fargesia. The morphology of this new species is similar to F. fractiflexa and Yushania polytricha, but differs in its ratio of culm leaf sheath length to internode length, shape of blade, foliage leaf dimensions, and distinct transverse veins. Hitherto, this new species is the smallest of Fargesia species found and recorded. According to the IUCN Red List Categories and Criteria (IUCN 2024), it meets the criteria to be listed as Critically Endangered (CR).